2008
DOI: 10.1016/j.bbrc.2007.10.174
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Escherichia coli K1 bound to human brain microvascular endothelial cells

Abstract: Escherichia coli K1 is the most common Gram-negative organism causing neonatal meningitis. Binding to human brain microvascdular endothelial cells (HBMEC) is an essential step for E. coli K1 traversal of the blood-brain barrier. In this study, we examined expression profiles of E. coli K1 strain RS218 during its binding to HBMEC. Comparison of HBMEC-bound E. coli K1 with collagenbound E. coli revealed more than one hundred genes whose expression patterns were significantly changed in HBMEC-bound E. coli K1, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In contrast to IPECs, NMEC strains are associated with high mortality rates, are genetically closely related, express a number of well-characterized fitness factors and belong to only a few serotypes of which O18:K1:H7 is widely spread and the most studied serotype [ 71 ]. Transcriptome analysis has revealed that the expression level of the fliI gene is significantly increased in NMEC associated with HBMEC cells compared to NMEC not associated with cultured cells [ 72 ]. Further analysis indicated that the H7 flagellum of E. coli O18:K1:H7 may be involved in NMEC pathogenesis.…”
Section: Flagellum-mediated Adhesionmentioning
confidence: 99%
“…In contrast to IPECs, NMEC strains are associated with high mortality rates, are genetically closely related, express a number of well-characterized fitness factors and belong to only a few serotypes of which O18:K1:H7 is widely spread and the most studied serotype [ 71 ]. Transcriptome analysis has revealed that the expression level of the fliI gene is significantly increased in NMEC associated with HBMEC cells compared to NMEC not associated with cultured cells [ 72 ]. Further analysis indicated that the H7 flagellum of E. coli O18:K1:H7 may be involved in NMEC pathogenesis.…”
Section: Flagellum-mediated Adhesionmentioning
confidence: 99%
“…A study comparing the gene expression patterns of HBMEC-associated versus non-associated E. coli with E. coli DNA microarray demonstrated that flagella play an important role in E. coli binding to HBMECs (66, 67). This concept is supported by the demonstration (a) that the mutant deleted of fliC was significantly defective in binding to and invasion of HBMECs, and this defect was restored by complementation with wild type fliC , (b) that recombinant flagellin (FliC) binds directly to the surface of HBMECs and (c) that exogenous recombinant flagellin inhibits E. coli binding to HBMECs (66).…”
Section: E Coli Penetration Of the Blood-brain Barriermentioning
confidence: 99%
“…The CGH was also utilized to examine the distribution of the eight RDIs that are relevant to the pathogenesis of E. coli meningitis among representative meningitis-causing E. coli isolates (67). RDI 16 harbors the K1 capsule biosynthesis gene cluster and, as expected, is present in all of the meningitis isolates.…”
Section: The Pathogenesis Of E Coli Meningitis: Functional Genomic Amentioning
confidence: 99%
“…Thus, ability to resist serum is likely an important virulence trait for both NMEC and APEC [9]. Although transcriptome and proteome approaches have been used to explore ExPEC pathogenesis [10][11][12][13][14][15], such approaches have rarely been used to probe ExPEC host specificity [16].…”
Section: Introductionmentioning
confidence: 99%